2003
DOI: 10.1016/s0960-9822(03)00166-0
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism for Activation of the Protein Kinase Aurora A

Abstract: Segregation of chromosomes during mitosis requires interplay between several classes of protein on the spindle, including protein kinases, protein phosphatases, and microtubule binding motor proteins [1-4]. Aurora A is an oncogenic cell cycle-regulated protein kinase that is subject to phosphorylation-dependent activation [5-11]. Aurora A localization to the mitotic spindle depends on the motor binding protein TPX2 (Targeting Protein for Xenopus kinesin-like protein 2), but the protein(s) involved in Aurora A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
381
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 338 publications
(400 citation statements)
references
References 28 publications
12
381
0
Order By: Relevance
“…2 and 3) and MLN8054, 19 demonstrates that it too is due to an autophosphorylation mechanism, as previously inferred from biochemical experiments with the Xenopus enzyme. 5,29,34 Interestingly, we found that pThr288 (active) Aurora A was specifically targeted to the centrosome during mitosis (Fig. 5D); this location is therefore a cytological marker of the activated kinase, and is likely to be enriched with Aurora A substrates that control spindle assembly.…”
Section: Discussionmentioning
confidence: 82%
“…2 and 3) and MLN8054, 19 demonstrates that it too is due to an autophosphorylation mechanism, as previously inferred from biochemical experiments with the Xenopus enzyme. 5,29,34 Interestingly, we found that pThr288 (active) Aurora A was specifically targeted to the centrosome during mitosis (Fig. 5D); this location is therefore a cytological marker of the activated kinase, and is likely to be enriched with Aurora A substrates that control spindle assembly.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, it was important to inhibit Aurora A kinase activity more specifically. Previous work has demonstrated that TPX2 is an activator of Aurora A present in Meta II oocytes that does not activate Aurora B (11). Therefore, we specifically impaired Aurora A activity by ablation of TPX2 with antisense oligonucleotides.…”
Section: Resultsmentioning
confidence: 94%
“…TA, transactivation domain; DNABD, DNA binding domain; OD, oligomerization domain. from this laboratory had identified TPX2 as an activator of Aurora A present in Meta II (cytostatic factor-arrested) Xenopus egg extracts (11), and the binding site for TPX2 on Aurora A has been well characterized both at the structural level and by mutagenesis (12-14, 43, 44). Our data here show that the level of TPX2 markedly increases during maturation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used okadaic acid, which is known to induce premature mitosis, as a stimulus for activation of PBK/TOPK. Interestingly, previous reports indicated that okadaic acid induced Ser 10 phosphorylation of histone H3 through inhibition of protein phosphatases (28,29). For example, Aurora-A is deactivated by protein phosphatase 2A (PP2A), but to be reactivated by its autophosphorylation through binding with TPX2 (targeting protein for Xenopus kinesin-like protein 2) protein that impairs the activity of PP2A (29).…”
Section: Discussionmentioning
confidence: 99%